PRESERVICE EFL TEACHERS’ PERCEPTION TOWARD THE TEACHING OF ESSAY WRITING DURING PANDEMIC - Laila Fitria Wibisono; Ana Ahsana El Sulukiyyah; Barotun Mabaroh (Erudio Journal of Educational Innovation, 2021)
Writing is a skill to improve students’ ideas on paper that English learners should master. Writing can train students’ thoughts on their minds. Having the ability to write well is important because it can be used to express the student’s thoughts. But most students consider writing difficult because they have to pay attention to grammar, vocabulary, and punctuation. The purpose of this study is to find out the students’ perceptions on the teaching of essay writing. This research focused on teaching English of Essay Writing subject in this Pandemic of COVID 19. The research was conducted in the fourth semester of the PGRI Wiranegara University academic year 2019 which were consist of 30 students. There were 4 males and 26 females. The researcher used quantitative design focused on survey. The researcher used a saturated sampling technique that is takes all populations as the sample. The research instrument was the questionnaire which consists of twenty questions. The result showed that the lecturer should pay more attention to the media used in the teaching of essay writing, then the learning facilities on the teaching of essay writing were so far good enough, but the use of ICT for the media was needed to be improved. Furthermore, the learning facilities during the teaching of essay writing were good and then the lecturer’s support was very good. The researcher suggested the lecturer could give better teaching performance toward the media used and learning facilities. PRESERVICE EFL TEACHERS’ PERCEPTION TOWARD THE TEACHING OF ESSAY WRITING DURING PANDEMIC